Smart library architecture based on internet of things (IoT) and software defined networking (SDN) - Zhou, Qi (Heliyon, 2024)
Internet of Things (IoT) is being widely developed in various fields, and its penetration rate in daily life is continuously increasing. The nature of the social function of objects and giving them an identity has made it possible to successfully integrate this technology into many traditional systems and improve their performance by automation. Libraries are one of the most obvious examples of smartening by IoT architecture. So far, various architectures have been presented for smartening libraries through IoT technology. However, a low-cost and ideal architecture that can cover all the requirements in a wide range of smart library applications has not been provided. This article attempts to fill some of the existing research gaps in this field by presenting a new architecture for smartening libraries. In the proposed method, Software Defined Networking (SDN) is used to reduce implementation costs and improve the management process of network components. In this architecture, the communication platform of network active objects is formed based on a cluster-based topology. Also, passive Radio Frequency IDentification (RFID) tags are utilized to manage books and library property. Two stages of evaluation have been conducted for the suggested method's performance: actual deployment and computer simulations. Based on the findings, it can be concluded that this study has succeeded in creating an effective and affordable design for smart libraries, which is a major advancement over conventional libraries.